2018
DOI: 10.1002/anie.201803983
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Control of the Conformational Landscape of Self‐Assembling Peptides

Abstract: Post-translational modification is a common mechanism to affect conformational change in proteins, which in turn, regulates function. Herein, this principle is expanded to instruct the formation of supramolecular assemblies by controlling the conformational bias of self-assembling peptides. Biophysical and mechanical studies show that an engineered phosphorylation/dephosphorylation couple can affectively modulate the folding of amphiphilic peptides into a conformation necessary for the formation of well-define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…Regardless of their difference in composition and secondary structure, most of these peptide hydrogelators self-assembled into one-dimensional fibrils, which further entangled with each other through salt bridge, hydrogen bond, and electrostatic attraction to form three-dimensional networks and therefore hydrogels40, 45, 46, 47. Additional functional groups such as targeting ligands 48 , enzyme-responsive groups49, 50, 51, drugs52, 53, fatty acids54, 55, DNA 56 , chelator 57 , fluorophores 58 can be integrated into peptide gelators without disturbing their capability in hydrogel formation. These peptide-based hydrogels have found broad biomedical applications in areas, such as tissue engineering 59 , drug delivery 60 and imaging58, 61.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of their difference in composition and secondary structure, most of these peptide hydrogelators self-assembled into one-dimensional fibrils, which further entangled with each other through salt bridge, hydrogen bond, and electrostatic attraction to form three-dimensional networks and therefore hydrogels40, 45, 46, 47. Additional functional groups such as targeting ligands 48 , enzyme-responsive groups49, 50, 51, drugs52, 53, fatty acids54, 55, DNA 56 , chelator 57 , fluorophores 58 can be integrated into peptide gelators without disturbing their capability in hydrogel formation. These peptide-based hydrogels have found broad biomedical applications in areas, such as tissue engineering 59 , drug delivery 60 and imaging58, 61.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the morphology of the assembled peptide had a remarkable role on the activity. Fiber‐like morphology accessed after about 15 days of assembly showed about 50 % lower activity compared to the activity seen in case of the matured nanotubes assembled for 30 days (see Table S1) . To probe this difference, the binding capabilities of C10‐FFVK , based on their states of assembly, were investigated.…”
Section: Figurementioning
confidence: 99%
“…At high concentration, the peptide grossly disrupts the membrane causing lysis and at concentrations below its lytic IC 50 , DVD‐1P acts as a cell‐selective penetrating peptide. We previously showed that dephosphorylation can control the self‐assembly and subsequent gelation of hairpin peptides . Although the exact molecular mechanisms of the cell penetrating and lytic activities of DVD‐1P are not known, they could involve self‐assembly at the cell surface given the high propensity of β‐hairpin amphiphiles towards self‐association.…”
Section: Figurementioning
confidence: 99%